Hak atas Informasi Pemadaman Listrik dan Pembayaran Kompensasi Ditinjau dari Hukum Positif - Rizki Triyadi; Tatty Aryani Ramli (Jurnal Riset Ilmu Hukum, 2022)
Abstract. Law Number 8 of 1999 concerning Consumer Protection have the right to information regarding the conditions and guarantees for the goods or services they use from business actors and by providing information on power outages, consumers can reduce losses by preparing alternative sources of electricity. In their economic activities and electricity providers are basically required to provide information on power outages no later than 24 (twenty four) hours before a power outage is carried out to consumers and this is regulated in Government Regulation Number 14 of 2012 concerning Electricity Supply Business Activities. In addition, consumers have rights which are lex specialist regulated in Law Number 30 of 2009 concerning Electricity, namely the right to obtain compensation and compensation due to a power outage to PT PLN,, but compensation and compensation can only be given if the power outage is caused by a power outage. due to negligence or error of the electricity provider while the power outage is caused by maintenance of electrical installations or repairs due to natural disaster disturbances, consumers are not entitled to claim compensation or compensation from PT PLN (Persero) and consumers are very difficult to claim compensation and compensation. These research were examined using a normative juridical approach and a descriptive analytical research specification. Abstrak. Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen, mempunyai hak atas informasi mengenai kondisi dan jaminan atas barang atau jasa yang digunakannya dari pelaku usaha dan dengan pemberian informasi pemadaman listrik tersebut konsumen dapat menekan kerugian dengan mempersiapkan sumber daya pengganti listrik dalam aktivitas ekonominya dan penyedia tenaga listrik pada dasarnya diharuskan untuk melakukan pemberian informasi pemadaman listrik paling lambat 24 (dua puluh empat) jam sebelum pemadaman listrik dilakukan kepada konsumen dan hal tersebut diatur dalam Peraturan Pemerintah Nomor 14 Tahun 2012 Tentang Kegiatan Usaha Penyediaan Tenaga Listrik. Selain itu konsumen mempunyai hak yang secara lex specialist diatur dalam Undang-Undang Nomor 30 Tahun 2009 Tentang Ketenagalistrikan yaitu hak untuk mendapatkan ganti rugi dan kompensasi akibat pemadaman listrik kepada PT PLN (Persero), namun pemberian kompensasi dan ganti rugi tersebut hanya dapat diberikan apabila pemadaman listrik disebabkan oleh kelalaian atau kesalahan petugas penyedia tenaga listrik sedangkan pemadaman listrik yang disebabkan oleh pemeliharaan instalasi listrik atau perbaikan akibat gangguan bencana alam, konsumen tidak berhak menuntut ganti rugi atau kompensasi kepada PT PLN ( Persero) dan konsumen sangat sulit untuk dapat menuntut ganti rugi dan kompensasi. Penelitian ini lakukan dengan metode pendekatan yang bersifat yuridis normatif dan spesifikasi penelitian yang bersifat deskriptif analitis.